Protection of Video Packets over a Wireless Rayleigh Fading Link: FEC versus ARQ. (6th July 2008) - Neckebroek Neckebroek, Julie Julie; Vanhaverbeke Vanhaverbeke, Frederik Frederik; De Vleeschauwer De Vleeschauwer, Danny Danny; Moeneclaey Moeneclaey, Marc Marc
Abstract : Video content can be provided to an end user by transmitting video data as a sequence of internet protocol (IP) packets over the network. When the network contains a wireless link, packet erasures occur because of occasional deep fades. In order to maintain a sufficient video quality at the end user, video packets must be protected against erasures by means of a suitable form of error control. In this contribution, we investigate two types of error control: (1) forward error correction (FEC), which involves the transmission of parity packets that enables recovery of a limited number of erased video packets, and (2) the use of an automatic repeat request (ARQ) protocol, where the receiver requests the retransmission of video packets that have been erased. We point out that FEC and ARQ considerably reduce the probability of unrecoverable packet loss, because both error control techniques provide a diversity gain, as compared to the case where no protection against erasures is applied. We derive a simple analytical expression for the diversity gain resulting from FEC or ARQ, in terms of the channel coherence time, the allowable latency, and (for FEC) the allowable overhead or (for ARQ) the time interval between (re)transmissions of copies of a same packet. In the case of HDTV transmission over a 60 GHz indoor wireless link, ARQ happens to outperform FEC.